Estimate of water connection to soil without water compressor when using sprinkler irrigation in the conditions of the lower alkhapur basin (Journal of Hama University, 2020)
The research was carried out in the field and climatic conditions of the lower khabur basin area with the aim of estimating the water connection of the soil without a water compressor when using the spray irrigation method. After conducting a series of 14 experiments on soils of different textures, the most important results were as follows:1 - Variation in the strength of the soil between clay and heavy clay where the highest percentage of physical clay reached 79.37%.• The majority of the soil of the lower khabur basin is very low in value for water delivery. It is suitable for spraying irrigation only after soil surface improvement procedures for water delivery.3 - There is no relationship between the strength of the soil and water conduction, and the speed of water connection of irrigation water by spraying is closely related to the physical state of the soil.4 - The abundance of spraying ranges between (0.40 - 1.84) mm/d, and the irrigation rate is (430-508) m3/h for a depth of (0-50) cm, while the rate of irrigation that does not constitute a water erosion of the soil surface ranges between (89.1-303.1) m3/h. In the end, we recommend spraying at low air speed hours, lower temperature (early morning and evening) and the use of sprinklers at an angle of 12-15 degrees in high wind yams, and the choice of sprinklers that give the permitted abundance, and do not lead to soil erosion.